The effects of somaclonal variation on morphological and DNA changes of Musa acuminata cv. Berangan (AAA) through micropropagation - Muslim Razani (2019)
Banana cv. Berangan is among the most important fruit plants in Malaysia with most of the planting material produced by tissue culture technique in commercial laboratories in Malaysia. However, banana tissue culture can potentially produce somaclonal variation after 7th subculture. Therefore, this study aimed to use benzylaminopurine (BAP) in the laboratory using a long cycle of time to detect somaclonal variation on morphological and genetic changes of banana cv. Berangan. The effects of different concentrations of BAP using banana cv. Berangan were investigated after 10th until 25th subculture for morphologies and genetic changes at the molecular level. The highest shoot multiplication was 22.1 ± 2.51 at 20th subculture for 5 mgL-1 of BAP treatment. RAPD analysis using randomized primers were compared between different morphology formed on different treatment like normal shoot, rosette-like structure and scalp after 20th subculture. The result inferred that there could be genetic changes in banana cultured using different BAP treatments. In this study, only two primers OPA19 and OPU06 showed variations in RAPD analysis. The experiment continued to further explore the potential of tissue culture explant originated from the scalp formed from the previous high BAP concentration treatment. Scalps were cultured into MS medium with different concentrations of BAP (0, 5, 10 and 15 mgL-1). The result showed that the scalp culture was able to revive to normal shoot and had the highest number of shoots in control treatment. Similarly, RAPD analysis suggested that there were genetic variations exist after the scalp developed into normal shoot in comparison to the other treatments. A BLAST analysis of the 276bp sequence of OPA19 primer was revealed to be homologous to fragments of the Musa acuminata clone MuG9, genomic sequence. The RAPD-SCAR marker was developed between control and BAP treatments based on OPA19 primer at 276 bp. This marker was validated by previous treatments. The results indicated a high degree of specificity of the marker, which was able to differentiate between control and BAP treatments. RDA analysis showed there was no genetic difference between the clones despite the observed phenotypic variation at tissue culture stages. However, the genetic differences were detected using RAPD analysis. The result showed that the RDA method was not sensitive enough to detect genetic variation among the clones. Moreover, RDA was proven successful to isolate the genetic differences between other cultivar bananas. These results suggested that the technique was able to isolate genome difference but not sensitive enough to isolate genetic difference among clones derived from the same line.